Indonesia's Carbon Trading as a Decarbonization Effort in Achieving the Enhanced Nationally Determined Contribution (ENDC) Target - Hadi, Kharren; Shalmont, Jerry (Universitas Negeri Semarang, 2025)
Carbon trading is one of the instruments in efforts to reduce emissions and encourage decarbonization. As a country with significant emissions, Indonesia contributes to global emissions reductions through carbon trading mechanisms conducted directly or through the Indonesia Carbon Market (IDXCarbon). However, carbon trading in Indonesia faces challenges such as lack of participation and issues that influence businesses decision to participate. This study aims to analyze the causes of low carbon trading in Indonesia and evaluate companies' efforts to reduce emissions, using empirical normative research methods, as well as qualitative data analysis with inductive methods. The results show that Indonesia's carbon trading is currently mandatory for the energy sector - power generation subsector, especially coal-fired power plants as the largest emission-contributing sector. While other sectors are still implementing carbon trading voluntarily. However, the obligation has not been followed by strict sanctions such as fines, but only administrative sanctions which are considered less effective. Therefore, there is a need for additional arrangements regarding fines. In addition, former President Joko Widodo's statement at the inauguration of IDXCarbon that Indonesia's carbon trading potential through the carbon exchange could reach Rp3,000 trillion has not been optimized, as evidenced by the low frequency of transactions and limited market participation. On the other hand, carbon trading has also not become the main choice for listed companies as a form of decarbonization, but only as an additional option to reduce their emissions.